Islamic Legal Reform and Democratic Values: Philosophical Foundations and Contemporary Challenges - Declan Patrick Byrne (Vifada Assumption Journal of Law, 2025)
This article explores the philosophical foundations and contemporary challenges of Islamic legal reform within democratic systems. As many Muslim-majority nations continue to negotiate the place of Islamic law in modern governance, tensions often emerge between traditional jurisprudence, state constitutionalism, and universal democratic norms. This study examines how key philosophical principles—such as justice, public welfare (maslahah), human dignity, and rational deliberation—serve as the normative basis for reconciling Islamic legal reasoning with democratic values. Employing a qualitative approach grounded in normative legal theory and comparative analysis, the paper highlights how reformist thinkers reinterpret classical concepts like ijtihad, maqāṣid al-sharī‘ah, and shura to support participatory governance, equality before the law, and protection of fundamental rights. Contemporary challenges, including politicization of religion, constitutional ambiguity, rising identity-based populism, and institutional reluctance toward legal modernization, are critically assessed to show why reform efforts often face resistance. The article argues that sustainable Islamic legal reform requires strengthening philosophical coherence, promoting inclusive interpretation, and enhancing institutional capacity within democratic frameworks. Ultimately, this study proposes a harmonization model in which Islamic legal ethics support democratic principles without eroding religious authenticity or constitutional stability.